Balancing the strength and toughness in delignified bamboo through the changing of silicon composition - You Wang; Shuyu Jia; Zhe Ling; Jianfeng Ma; Xinxin Ma; Changhua Fang (Materials & Design)
The partial removal of lignin from bamboo materials, a prevalent method to soften the material for plastic forming. It increases bending toughness and improves forming quality, albeit at the expense of load-bearing capacity. This study employs an innovative approach using deep eutectic solvent pretreatment on bamboo green strips (BGS) to establish a balance between strength and toughness, resulting in a significant enhancement of the elastic modulus. The mechanical properties of the DES-treated BGS displayed notable improvements compared to bamboo timber strips (BTS) and bamboo yellow strips (BYS), which either showed no enhancement or suffered degradation after extended treatment durations. Notably, BGS treated for one hour exhibited increases of 8.22 % in flexural toughness and 33.45 % in elastic modulus, while strength diminished by a mere 5.72 %. Concurrently, its porosity increased by 29.36 %, predominantly in the mesopore range. In addition, the crystallinity of the treated BGS increased, whereas the grain size decreased. Silicon-aluminum compounds form on the outer surface of BGS, along with an increase in silicon oxide content, contributed to the observed improvements in stiffness and toughness. These works suggest a novel method for balancing modulus and strength of bamboo structural units, with potential applications in architecture, furniture and transportation sectors.